Efektifitas Azotobacter chroococcum dalam Proses Bioremediasi Tanah Terkontaminasi Limbah Minyak Bumi Menggunakan Bakteri Petrofilik - Suryatmana, Pujawati; Latifah, Tipah; Kamaluddin, Nadia Nuraniya; Hindersah, Reginawanti; Setiawati, Mieke Rochimi (Soilrens, 2025)
Bioremediation is a method for restoring land contaminated by waste, utilizing the activity of microorganisms to reduce and eliminate the toxicity levels of pollutants. A major challenge in the bioremediation of petroleum waste is the extremely low solubility of petroleum and the limited capacity of hydrocarbon-degrading bacteria. This study aims to examine the potential of petrophilic bacteria and Azotobacter chroococcum in enhancing hydrocarbon degradation efficiency, the viability of petrophilic bacteria and Azotobacter spp., and soil acidity characteristics (pH) during the bioremediation process. The experiment used a factorial randomized complete block design (RCBD) with two factors and three replications. The first factor was the type of petrophilic bacteria which consisted of two levels: (a0) without petrophilic bacteria, and (a1) 2% petrophilic bacterial inoculation per waste load. The second factor was the dose of Azotobacter chroococcum, consisted of four levels: (b0) without A. chroococcum, (b1) 0.5%, (b2) 1%, and (b3) 1.5% A. chroococcum. The results showed that soil pH decreased from a range of 8–9.1 to 6.6–6.7 after the bioremediation process, despite no significant differences were detected between treatments. Biodegradation efficiency increased with the application of A. chroococcum and petrophilic bacteria compared to the control, although no significant differences were found between the bacterial treatments. The application of A. chroococcum at 1% and 1.5% significantly increased Azotobacter population density. Overall, petrophilic bacteria and A. chroococcum demonstrated high effectiveness in improving biodegradation efficiency.